Spatial interaction of the tourist dynamics of the Magical Towns of Zacatlán and Chignahuapan, Puebla - Castro Pérez, Alicia Mariana Penélope; Quintero Venegas, Gino Jafet (Investigaciones Geográficas, 2022)
Zacatlán and Chignahuapan are two Magical Towns that depend on the tourist fluxes from the two closest urban centers: Mexico City and Puebla. Both localities, located in Puebla, maintain a spatial interaction supported by complementarity above the competition, as a result of the valued tourist resources, the type of services offered and the geographical proximity between them, which is a comparative advantage. In this text, elaborated from mixed methodologies, it is evident how spatial complementarity has been built from the presence of common visitors, the development of tourist infrastructure, and the seasonal behavior of tourist flows towards the two locations, where the spatial interaction generates a complementarity in which the two places function as one spatial entity.